Adipose-Derived Molecules–Untouched Horizons in Alzheimer’s Disease Biology - Pichiah, P. B. Tirupathi; Sankarganesh, Devaraj; Arunachalam, Sankarganesh; Achiraman, Shanmugam (Frontiers in Aging Neuroscience, 2020)
The global incidence of Alzheimer’s disease (AD) is on the rise with the increase in obesity and metabolic disease epidemic. Obesity is co-morbid with the increase in mass of adipose tissue, which secretes numerous molecules that are biologically important. Obesity and its associated conditions are perhaps involved in the causative pathway of AD. Immunologically important cytokines such as IL-1β, IL-10, and IL-18, which are released by adipose tissue, are also found to be associated with AD. Besides, the expression of IL-6, IFNγ, and TNF alpha are also associated with AD. Ang-I and Ang-II are found to mediate the progression of AD. Complement factors B, C4b, and H are differentially expressed in AD. Overall, several adipocyte-derived cytokines are found to be dysregulated in AD, and their role in AD remains to be studied. The induction of autophagy is a very promising strategy in the treatment of AD. A variety of adipose-derived molecules have been shown to modulate autophagy. However, very little literature is available on the role of adipose-derived molecules in inducing autophagy in microglial cells of AD. Understanding the role of adipose-derived molecules in the development of AD, especially in the induction of autophagy, would open up new avenues in devising strategies for the treatment of AD.